Redesigning the Multi-purpose Community Hall in Petompon, Semarang - Santoso, Eko Budi; Diharto; Setyowati, Wiwit; Wibowo, Ardiyan Adhi; Savanti, Fisa; Fahrudin; Hidayat, Vicky Rosyid; Fadila, Salwa Nur; Maulita, Sintia Putri (Universitas Negeri Semarang, 2024)
The multi-purpose community hall is a crucial facility that fosters community activities, cultural engagement, and public services. The Petompon Sub-district Hall in Semarang requires a redesign to enhance its functionality, accessibility, and adaptability. This study presents a comprehensive approach to redesigning the hall, focusing on spatial optimization, adaptive reuse, material updates, and user-centered design principles. The results highlight the importance of integrating modern architectural practices while preserving the building's structure to create a functional and inclusive community space.